2004
DOI: 10.3732/ajb.91.6.804
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome numbers, meiotic behavior, and pollen viability of species of Vriesea and Aechmea genera (Bromeliaceae) native to Rio Grande do Sul, Brazil

Abstract: Chromosome number, meiotic behavior, and pollen viability were analyzed in 15 species of two genera, Vriesea and Aechmea, native to Rio Grande do Sul, Brazil. This study is the first cytogenetic analysis of these taxa. The chromosome numbers are all n = 25, consistent with the proposed base number of x = 25 for Bromeliaceae. All examined taxa displayed regular bivalent pairing and chromosome segregation at meiosis. Observed meiotic abnormalities include univalents in metaphase I; missing or extra chromosomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…All metaphase I cells were regular with predominant bivalent pairing indicating that plants of these two species are potentially interfertile. Regular meiosis was also reported for species of two other diploid bromeliad genera Vriesea and Aechmea (Palma-Silva et al 2004. This is the first report of meiotic chromosome pairing for a polyploid species.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…All metaphase I cells were regular with predominant bivalent pairing indicating that plants of these two species are potentially interfertile. Regular meiosis was also reported for species of two other diploid bromeliad genera Vriesea and Aechmea (Palma-Silva et al 2004. This is the first report of meiotic chromosome pairing for a polyploid species.…”
Section: Resultsmentioning
confidence: 72%
“…In the Bromeliaceae, cytogenetic studies are rare and chromosome numbers have been reported for no more than 12% of the species (Lindschau 1933;Gauthé 1965;Weiss 1965;Marchant 1967;Sharma & Ghosh 1971;McWilliams 1974;Brown et al 1984;Varadarajan & Brown 1985;Brown & Gilmartin 1986, 1989Lin et al 1987;Brown et al 1997;Cotias-de-Oliveira et al 2000Ramírez-Morillo & Brown 2001;Palma-Silva et al 2004;Bellintani et al 2005;Gitaí et al 2005). The chromosomes are small with sizes varying between 0.23 mm and 1.5 mm (Cotias-de-Oliveira et al 2000;Ceita et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, meiotic studies carried out by Palma‐Silva et al . 2004; 2008) reported meiotic irregularities in Vriesea and Aechmea , including irregular pairing and observations of univalents, which may lead to a misinterpretation of the bivalent number during meiosis, especially in taxa with small chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Even basic cytogenetic studies in this family are scarce, and only approximately 10% of the species have had their chromosome numbers reported. In Vriesea, a genus that comprises approximately 250 species, chromosome numbers have been recorded for no more than 24 species (Gauthè 1965; Weiss 1965; Marchant 1967; Brown & Gilmartin 1989; Palma‐Silva et al . 2004).…”
Section: Introductionmentioning
confidence: 99%